2015
DOI: 10.4103/1673-5374.156979
|View full text |Cite
|
Sign up to set email alerts
|

CX3 chemokine receptor 1 defciency leads to reduced dendritic complexity and delayed maturation of newborn neurons in the adult mouse hippocampus

Abstract: Previous studies have shown that microglia impact the proliferation and differentiation of neurons during hippocampal neurogenesis via the fractalkine/CX3 chemokine receptor 1 (CX3CR1) signaling pathway. However, whether microglia can influence the maturation and dendritic growth of newborn neurons during hippocampal neurogenesis remains unclear. In the present study, we found that the number of doublecortin-positive cells in the hippocampus was decreased, and the dendritic length and number of intersections i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…To further examine the role of microglia in obesity-induced cognitive decline, we used transgenic Cx3cr1 ϩ/Ϫ mice, in which one allele of Cx3cr1 is replaced with the gene for GFP (Jung et al, 2000). We decided to use heterozygous Cx3Cr1 ϩ/Ϫ instead of homozygous Cx3Cr1 Ϫ/Ϫ mice because greater abnormalities in hippocampal structure and cognitive behavior have been observed with the complete knock-out (Rogers et al, 2011;Xiao et al, 2015;Sellner et al, 2016). Consistent with what we observed for WT mice, adult Cx3cr1 ϩ/Ϫ mice fed HFD for 12 weeks were significantly heavier than control-fed Cx3cr1 ϩ/Ϫ mice (Fig.…”
Section: Hfd Induces Obesity In Cx3cr1-deficient Micementioning
confidence: 99%
“…To further examine the role of microglia in obesity-induced cognitive decline, we used transgenic Cx3cr1 ϩ/Ϫ mice, in which one allele of Cx3cr1 is replaced with the gene for GFP (Jung et al, 2000). We decided to use heterozygous Cx3Cr1 ϩ/Ϫ instead of homozygous Cx3Cr1 Ϫ/Ϫ mice because greater abnormalities in hippocampal structure and cognitive behavior have been observed with the complete knock-out (Rogers et al, 2011;Xiao et al, 2015;Sellner et al, 2016). Consistent with what we observed for WT mice, adult Cx3cr1 ϩ/Ϫ mice fed HFD for 12 weeks were significantly heavier than control-fed Cx3cr1 ϩ/Ϫ mice (Fig.…”
Section: Hfd Induces Obesity In Cx3cr1-deficient Micementioning
confidence: 99%
“…Independently of its actions on microglia, IL-34 can also activatetheCSF-1R expressed on capillary endothelial cells and restore BBB integrity by upregulating tight junction proteins [99]. The roles of microglia in neuronal development are based on [35,57,8790,92,9497]. Abbreviations: Cb, cerebellum; CC, corpuscallosum; Cx, cortex; Hp, hippocampus; MΦ, macrophage; M1–M3 denote microglial activation states with M1 representing inflammatory microglia; M2, alternatively activated, trophic microglia; and M3 rapidly proliferating microglia that are not M1-or M2- polarized; NB, neuroblast; OB, olfactorybulb; RMS, rostral migratory stream; St, striatum; SVZ, subventricular zone; YS, yolk sac.…”
Section: Figurementioning
confidence: 99%
“…Indeed, fractalkine signaling was shown to regulate learning and memory (Maggi et al, 2011), social behaviors (Zhan et al, 2014), and microglial neurotoxicity during inflammation and stroke (Cardona et al, 2006; Tang et al, 2014). Under epileptic conditions, recent studies found that fractalkine deficiency resulted in reduced dendritic complexity and delayed maturation of adult newborn neurons (Xiao et al, 2015). However, the exact role of fractalkine signaling in seizure-induced microglia–neuron physical interactions has not been investigated.…”
Section: Introductionmentioning
confidence: 99%